VILLAGE-OWNED ENTERPRISE MANAGEMENT MODEL BASED ON GOOD GOVERNANCE: A STUDY OF VILLAGE-OWNED ENTERPRISES IN BOGOR REGENCY - Usman, Fadlil; Sjamsuddin, Sjamsiar; Mardiyono; Sujarwoto; Fuady, Muhammad Syahrul (Veredas do Direito, 2026)
This study examines the management model of Village-Owned Enterprises (BUMDesa) based on good Governance in Bogor Regency. The main focus of the study is to integrate the principles of good Governance, namely Accountability, Rule of Law, Transparency, Professionalism, Effectiveness and Efficiency, Participation, and Responsiveness in BUMDesa governance. Organizational responsiveness is an important factor in increasing public trust and ensuring that the services provided are in accordance with local needs. Human resources (HR) are a key element in the successful implementation of good Governance. However, low levels of education, lack of experience, and age factors of BUMDesa managers are often obstacles to the implementation of good Governance. By adapting Lawrence Green's theory, this study analyzes the predisposing, enabling, and driving factors in BUMDesa management. The novelty in this study includes an adaptive management model that considers local challenges, recommendations for the implementation of information technology-based Governance, and the use of a holistic approach in analyzing factors that influence BUMDesa governance. The results of the study indicate that the application of the responsiveness principle in BUMDesa governance improves operational efficiency, accelerates decision-making, and strengthens public trust. This research provides theoretical and practical contributions to the management of BUMDesa, especially in developing a more adaptive and sustainable governance model. The implication is that the results of the study can be a reference for other villages in Indonesia in improving responsive and innovative BUMDesa governance.